Capturing a locomotive. : a history of secret service in the late war - Pittenger, William, 1840-1904 (Digital Scanning, 2000)
Unlike other books from this time period dealing with historical aspects of the Civil War, Capturing a Locomotive focuses not only on the well known battles but rather portrays the personal accounts of the Union soldiers who carried out the mission into Confederate territory. The story details the dangerous capture of a railway train, the exciting chase that ensues and the final outcome of this group of brave men. Survivors of this mission were the first soldiers with the rank of Private to be awarded the Congressional Medal of Honor. No single story of the Civil War combines so many of the hidden underground elements that are rarely brought to the surface through traditional analysis of tactical warfare.